Neuroprotective Potency of Crocus sativum L. for Alzheimer’s Disease - L. Deore, Sharada; Vighne, R. C.; A. Baviskar, Bhushan; A. Kide, Anjali; A. Shende, Bhavana (Pharmacognosy Reviews)
“Alzheimer’s disease (AD) is recognised as the main cause of cognitive decline in the elderly.” Due to unpleasant complicacy, low patient compliance, short t1/2 and biologic restrictions these current therapeutic techniques are insufficiently effective.In AD decrease the level of acetylcholine (ACh) in the brain. Presently available drugs for AD temporarily relieve dementia symptoms by acting as an AChEI and NMDA receptor antagonist, but they cannot prevent or cure disease progression. The current emphasis of Alzheimer’s research is on creating antibodies to eliminate Aβ and tau protein clumps. Some medicinal plants, either in their raw form or as isolated compounds has been found to reduce the degenerative symptoms linked to Alzheimer’s illness. As a result, researchers are looking for novel, multi-targeted therapy strategies. The plant Crocus sativus is rich in biological and pharmacological properties, primarily antioxidant and anti-inflammatory. The findings show that C. sativum and its chemical ingredients might result to improve memory and cognitive impairment. Traditional medicine has defined the major qualities of this plant to the chemical constituents of saffron like colouring pigment also known as crocin, a natural apocarotenoid crocetin, aromatic saffranal and few phenolic components. Anti-convulsant, antioxidant, anti-diabetic, anti-apoptotic, anti-bacterial, anti-cancer, antigenotoxic, angiogenesis, anti-depressant, anti-inflammatory and other properties are found in C. sativus. Crocin is a water-soluble carotenoid, making it a unique antioxidant. It has been demonstrated to boost learning and memory while also protecting brain cells.
Keywords: Saffron; Neuroprotective; Alzheimer’s disease; Crocin; Carotenoid; Neurotransmitter; Neurodegenerative; Amyloid beta; Dementia; Antioxidant